UPAYA PENINGKATAN HASIL BELAJAR IPA MELALUI PENERAPAN MODEL COOPERATIVE LEARNING TIPE CIRC SISWA KELAS VIII 2 SEMESTER II SMPN 1 BUKIT BATU TA 2014/2015 - Siti Arbi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2015)
The fundamental problem of science teacher while teaching in class VIII 2 SMP Negeri 1 Bukit Batu are students less skilled think to learn, afraid to ask and argue and difficulties in solving the story, learning outcomes IPA quite low, and the props are still enough/less attractive and others. The achievement of value UH in the pre-cycle to all who completed 4 people (17.4%) and incomplete 19 (82.6%), and in the first cycle students completed 14 (60.8%) and 9 are not complete (39.2%), while in the second cycle students who completed 21 (91.3%) and incomplete is 8.7%. Through the implementation of this model seen an increase in the activities of teachers and students as well as student learning outcomes. The implications of this research can be used as a basis for the development of the next class research and can be used as an alternative learning models and improve cognitive, effective, and psychomotor.